Using GPT-4 for Financial Advice - Christian Fieberg; Lars Hornuf; David J. Streich (Center for Economic Studies and ifo Institute (CESifo), 2023)
We show that the recently released text-based artificial intelligence tool GPT-4 can provide suitable financial advice. The tool suggests specific investment portfolios that reflect an investor's individual circumstances such as risk tolerance, risk capacity, and sustainability preference. Notably, while the suggested portfolios display home bias and are rather insensitive to the investment horizon, historical risk-adjusted performance is on par with a professionally managed benchmark portfolio. Given the current inability of GPT-4 to provide full-service financial advice, it may be used by financial advisors as a back-office tool for portfolio recommendation.
Keywords: G00; G11; 330; GPT-4; ChatGPT; financial advice; artificial intelligence; portfolio management